PENGEMBANGAN MEDIA MINIATUR PADA MATA PELAJARAN FIQIH - Octaviani, Annisa; Pahrudin, Agus; Romlah, Listiyani Siti; Susanti, Agus (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop learning media in the form of miniature media for fiqh subjects to improve students' understanding of fiqh learning concepts that are practical. This research uses the R&D method with the ADDIE development model which includes 5 stages, including: Analysis, Design, Development, Implementation and evaluation. The subjects in this study were students of class VIII.D MTs PEMNU Talang Padang. Data collection instruments include media expert validation sheets, linguists and student response questionnaires. The validation results showed that the media developed were in the “very feasible” category with a percentage of 84% from media experts, 89% from material experts, 86% from fiqh teachers, 96% from linguists. In addition, the results of the students' response questionnaire showed a high level of interest and ease of learning in the use of miniature media developed. Thus, miniature media is effectively used in fiqh learning in strengthening students' concept understanding visually and contextually. ABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran berupa media miniatur mata pelajaran fiqih guna meningkatkan pemahaman peserta didik akan konsep-konsep pembelajaran fiqih yang bersifat praktis. Penelitian ini menggunakan metode R&D dengan model pengembangan ADDIE yang meliputi 5 tahapan, diantaranya: Analysis, Desain, Development, Implementation dan evaluation. Subjek dalam penelitian ini adalah peserta didik kelas VIII.D MTs PEMNU Talang Padang. Instrumen pengumpulan data meliputi lembar validasi ahli media, ahli bahasa dan angket respon peserta didik. Hasil validasi menunjukkan bahwa media yang dikembangkan masuk dalam kategori “sangat layak” dengan persentase perolehan sebesar 84% dari ahli media, 89% dari ahli materi, 86% dari guru fiqih, 96% dari ahli bahasa. Selain itu, hasil angket respon peserta didik menunjukkan tingkat ketertarikan dan kemudahan dalam belajar yang tinggi terhadap penggunaan media miniatur yang dikembangkan. Dengan demikian, media miniatur efektif digunakan dalam pembelajaran fiqih dalam memperkuat pemahaman konsep peserta didik secara visual dan konstekstual.